Failure Modes in Orthopedic Oncologic Reconstructive Surgery: A Review of Imaging Findings and Failure Rates - Anuj Shah; Fabiano N. Cardoso; Felipe Souza; Julien Montreuil; Juan Pretell-Mazzini; H. Thomas Temple; Francis Hornicek; Brooke Crawford; Ty K. Subhawong (Current Oncology)
Limb salvage surgeries utilizing endoprostheses and allografts are performed for a variety of oncologic conditions. These reconstructions can fail and require revision for many reasons, which are outlined and classified into mechanical failures (soft tissue failures, aseptic loosening, structural failure), non-mechanical failures (infection, tumor progression), and pediatric failures (physeal arrest, growth dysplasia). Distinct radiologic and clinical findings define specific failure subtypes but are sparsely illustrated in the radiology literature. Specifically, an understanding of the organizational structure of the failure modes can direct radiologists’ search for post-reconstruction complications, enhance an appreciation of their prognostic significance, and facilitate research by standardizing the language and conceptual framework around outcomes. The purpose of this review is to highlight the key radiologic findings and imaging studies of each failure mode in orthopedic oncologic reconstructive surgery in the context of risk factors, failure rates, prognosis and survival statistics, and clinical decision-making regarding chemotherapy, radiation, and revision surgery.